The prevalence of dental caries and its associated factors among preschool children in Huizhou, China: a cross-sectional study - Chen, Jieyi; Chen, Wanting; Lin, Lude; Ma, Haozhen; Huang, Fang (Frontiers in Oral Health, 2024)
BackgroundDental caries among preschool children were prevalent worldwide and had a significant impact on children and their families. Understanding its prevalence and risk factors helps to optimize the delivery of oral health care to the target population and promote their oral health ultimately. This cross-sectional study aimed to examine the prevalence of dental caries and its associated factors among 3- to 5-year-old children in Huizhou, Guangdong Province, China.MethodWe recruited children from 21 kindergartens adopting multistage sampling method. Two examiners performed oral examination. They assessed children's dental caries experience following the World Health Organization criteria. Children's dental caries activity, malocclusion, tonsil size and pH value of saliva were evaluated. Parental questionnaires collected child's sociodemographic background and oral-health-related behaviors. Data were analyzed by univariate analysis and logistic regression using SPSS.ResultsThis study invited 1,485 children and recruited 1,348 (53.2% boys) (response rate: 90.8%). Dental caries prevalence rate was 58.2% for 3-, 70.7% for 4-, 80.5% for 5-year-old and 72.9% for all recruited children. The mean dmft score (±SD) was 3.38 (±4.26) for 3-, 4.75 (±4.96) for 4-, 5.81 (±5.71) for 5-year-old and 4.99 (±5.02) for all children. Age, family status (singleton or not), monthly family income, mother and father's education level, tonsil grading score, spacing in dentition, Cariostat score (reflecting the caries activity), dental plaque index, duration of breastfeeding, dental visit experience, tooth brushing habits and sugary snacking before sleeping were statistically related to the prevalence of dental caries (p < 0.050) in univariate analysis. These factors were further analyzed in the regression model. The results of the final model indicated dental caries were associated with age (p < 0.001), Cariostat score (p < 0.001), spacing (p < 0.001), tonsil grading score (p = 0.013), singleton or not (p = 0.002), sugary snacking habit before bed (p < 0.001) and breast-feeding duration (p = 0.050).ConclusionDental caries was prevalent among 3-to 5-year-old preschool children in Huizhou, China. Children's age, caries activity, tonsil size, malocclusion, family background, sugary snacking habit and breast-feeding habit were related to the prevalence of dental caries. More emphasis should be placed on prevention targeting the risk factors from early life.